Discrimination by parity is a prerequisite for assessing obstetric outcome. (18th April 2012) - Foley, M; O'Herlihy, C; Robson, M
Abstract : Background: A PubMed search (2004-2011) yielded 115 abstracts on induction of labor of which 27(23.5%) specifically stated that the study was confined to nulliparas or multiparas, 23(20%) mentioned parity as a variable and 65 (56.5%) did not mention parity. The objective was to clarify the major differences between nulliparas and multiparas so that in future, labour outcomes would be reported separately for nulliparas and multiparas. Methods: Obstetric data were collated on a computer database on all patients at the time of delivery for the year 2009. Results: Among 9161 women (nulliparas, n=4407, multiparas, n=4754) there were 3882 nulliparas and 3563 multiparas (without scar) at term (> 37 weeks gestation). The caesarean section rate was significantly higher amongst nulliparas compared with multiparas for both spontaneous labor (195/2502; 7.8% vs. 25/2678; 0.9%) and induced labor (389/1311;29.7.%v.s.51/811; 6.3%, P<0.0001). The prelabor caesarean section rate was similar among both cohorts (69/3882;1.5%vs.74/3563;2.0%). Multiparas were significantly older (P< 0.01), had a higher BMI category (P<0.01) and although they had a higher range of birth weight, this was not significant. Significantly more nulliparas were induced compared with multiparas (1311/3882;33.9% vs. 811/3563(22.8%), P<0.001); induction for post-term pregnancy and spontaneous rupture of the membranes accounted for the most important differences (P< 0.001) and also contributed most to the higher caesarean rate among induced nulliparas. Conclusion: The results confirm the major differences between nulliparas and multiparas and provide unequivocal evidence that obstetric outcome should be reported separately by parity.